PROTECTIVE EFFECT OF LYCOPENE ON OXIDATIVE STRESS INDUCED BY DIFFERENT DOSES OF 2,3,7,8-TETRACHLORODIBENZO-p-DIOXIN IN BRAIN, LIVER, KIDNEY, AND HEART TISSUE OF RATS - Sakin, Fatih; Bulmus, Funda Gulcu; Servi, Kadir; Popa, Lacramioara (Soc Stiinte Farmaceutice Romania, 2011)
The aim of this study was to investigate the possible protective role of lycopene (LYC) on liver, kidney, heart, and brain in male rats exposed to different doses of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Forty-eight rats were divided into six groups. The first group received 0.5 mL corn oil as control; the second group was treated with 10 mg/kg bw/day LYC. Groups 3 and 4 were treated to 50 and 500 ng/kg bw/day of TCDD, respectively. Groups 5 and 6 were subjected to 50 and 500 ng/kg bw/day of TCDD along with 10 mg/kg bw/day of LYC, simultaneously. The duration of the experiment was 13 weeks. While the exposure to TCDD increased the levels of malondialdehyde (MDA), it decreased glutathione (GSH) levels, and superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) activities. However, LYC-treatment decreased the high MDA levels and increased GSH, SOD, GSH-Px, and CAT activities. In conclusion, LYC treatment decreased TCDD-induced lipid peroxidation and supported the antioxidant activity. It is suggested that LYC has a protective effect against oxidative stress induced by TCDD.
Keywords: dioxin; toxicity; oxidative stress; lycopene